Study to find out about various risk factors responsible for repeat acute exacerbation of COPD, which cause readmission within 90 days after admission in hospital due to acute exacerbation of COPD - Parihar, Sandeep kumar; Bharty, Sanjay Kumar; Patel, Brij Bihari; Patel, Vikas; Prakash, Brahma; Jain, Avinash (Asian Journal of Medical Sciences, 2023)
Background: Approximately 3.2 million global deaths occur each year due to chronic obstructive pulmonary disease (COPD), in which exacerbations of COPD remain a prevailing cause. Exacerbations requiring hospitalization are associated with high mortality, and mortality risk is increased with higher exacerbation frequencies. Aims and Objectives: This study aimed to prospectively identify the risk factors of COPD that cause readmission within 90 days after admission to the hospital due to acute exacerbations of COPD. Materials and Methods: An observational study conducted at the School of Pulmonary Excellence, NSCB Medical College, Jabalpur, from the duration of March 2021 to August 2022 with a sample size of 140 estimated through 56% prevalence of readmission rate in available literature. Study participants, including all patients, were readmitted within 90 days after admission due to acute exacerbation of COPD (post-bronchodilator FEV1/FVC <0.70). Data analysis was performed using IBM software SPSS 22.0 and statistical association with the confidence interval of 95% and P<0.05. Results: The majority of COPD cases were male (84%) and belonged to the 50–60 years of age group. There was a statistically significant (P=0.001) association between grades of dyspnea and readmission cases. Dyspnea among readmission patients was found to be 100%. The prevalence of CAT score >10 was 64% and <10 is 36% among readmission patients the association was highly significant and more exacerbation leads to more readmission. Conclusion: In the study, various clinical parameters were found statistically significant between the admission and readmission groups. These parameters were CAT score, previous hospitalization history, previous exacerbation history, SpO2, dyspnea grading, and co-morbidities. The lung function test was difficult to do due to many of readmitted patients were not in a condition to do spirometry.